Need Assessment Of Learning Inclusive Program For Students In Nonformal Of Early Childhood Education - Ari Putra (Department of Early childhood Education, 2018)
The concept of the inclusive program is an organized according to the ability and needs of students with the aim of learners to be successful and can optimize the potential within themselves. Currently, the inclusive program is newly embodied in formal education programs such as elementary, junior, and senior high schools. The current problem does not clear the maturity of the concept of the inclusive education program in non-formal education, especially in non-formal of early childhood education. This study aims to find out how the assessment process done by teachers in Bunayya Islamic preschooler finding out the source of learning needs such as students with special needs. The research method used is the qualitative method by using triangulation of subject, time, and place. The result of this research show that Bunayya Islamic preschooler make an initiative to create their own learning concepts without technical guidance such as inclusive curriculum development and lesson plans. Bunayya Islamic preschooler runs the learning program by planning, implementing and evaluating the needs of learning resources of children with special needs. The conclusion of this study are the teacher performs several steps such as the identification of special needs children, pre-qualification priorities and the development of the learning curriculum to adopted the learning interpretation and alternative program for preschoolers and parent’s concepts